Omental pedicle flaps following proctectomy: a systematic review. (November 2013) - Killeen, S.; Devaney, A.; Mannion, M.; Martin, S. T.; Winter, D. C.
Abstract Aim Abdominoperineal excision (APR) for cancer carries significant morbidity of the perineal wound. An omental pedicle graft has been used to fill the pelvis and limit attendant complications after radical extirpation of the anorectum. A review of the literature was conducted to determine whether omentoplasty following APR reduces perineal wound complications. Method Three major databases (PubMed, MEDLINE and the Cochrane Library) were searched. The review included original articles reporting outcomes after APR and omentoplasty from January 1950 to July 2012. Results Fourteen studies involving 891 patients (mean age 61 years, 59.8% men) were included. Median follow‐up was 13.5 months. A variety of omentoplasty techniques added a median of 20 min to the operating time. The mean rate of primary wound healing was 66.8%, time to wound healing 24 days and weighted mean wound infection rate 14.4% with omentoplasty compared with 50.1%, 79 days and 18.5% in patients having no omentoplasty. Conclusion Omental mobilization, transfer and buttressing of primary perineal repair following proctectomy reduces perineal wound morbidity with minimal additional operating time or flap‐associated morbidity.